2019
DOI: 10.2166/wst.2019.038
|View full text |Cite
|
Sign up to set email alerts
|

Modified xanthan gum for crystal violet uptake: kinetic, isotherm, and thermodynamic behaviors

Abstract: Modified xanthan gum (XG-AM-TTE) was employed as an adsorbent to study the adsorption behavior, thermodynamics and kinetics of crystal violet (CV) from an aqueous solution. Fourier transform infrared spectroscopy analysis indicates that the functional groups present in the adsorbent, such as carboxyl, ester and hydroxyl groups, are included on the external surface of the material, and these groups are potential active sites for interaction with CV. According to X-ray diffraction results, the structure of XG-AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…d -mannose is O -acetylated by pyruvic acid linked at positions 4 and 6, whereas the d -mannose linked to the backbone is O -acetylated by acetate groups at position 6. ,, Copious amounts of Xanthan gum are used in food industries as thickeners because of its high viscosity at low concentration also used in cosmetics and tooth paste industries among others. ,,, In recent years, Xanthan gum has been extensively modified to serve as a dye sorbent by many researchers. For example, acrylamide was grafted to Xanthan gum and incorporated with silica nanoparticles to capture dyes. , Other researchers grafted acrylamide to Xanthan gum and cross-linked with trimethylolpropane triglycidyl ether and used it as an adsorbent to capture the Crystal Violet dye . In another study, acrylic acid was grafted to Xanthan gum to adsorb the Rhodamine dye .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…d -mannose is O -acetylated by pyruvic acid linked at positions 4 and 6, whereas the d -mannose linked to the backbone is O -acetylated by acetate groups at position 6. ,, Copious amounts of Xanthan gum are used in food industries as thickeners because of its high viscosity at low concentration also used in cosmetics and tooth paste industries among others. ,,, In recent years, Xanthan gum has been extensively modified to serve as a dye sorbent by many researchers. For example, acrylamide was grafted to Xanthan gum and incorporated with silica nanoparticles to capture dyes. , Other researchers grafted acrylamide to Xanthan gum and cross-linked with trimethylolpropane triglycidyl ether and used it as an adsorbent to capture the Crystal Violet dye . In another study, acrylic acid was grafted to Xanthan gum to adsorb the Rhodamine dye .…”
Section: Introductionmentioning
confidence: 99%
“…16,25 Other researchers grafted acrylamide to Xanthan gum and cross-linked with trimethylolpropane triglycidyl ether and used it as an adsorbent to capture the Crystal Violet dye. 26 In another study, acrylic acid was grafted to Xanthan gum to adsorb the Rhodamine dye. 27 A sol−gel-derived Xanthan gum silica nanocomposite was used to capture cationic dyes.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on the chemical modification of xanthan gum by various techniques and the grafting of different groups are described in the literature [11,[15][16][17][18]. The nature of the grafted groups differentiates the structural characteristics of the polysaccharides due to various physicochemical and biological properties [19].…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers grafted acrylamide onto xanthan gum, cross-linked with trimethylolpropane triglycidyl ether and used it as an adsorbent to capture the crystal violet dye. 50 Njuguna et al reported on the synthesis of xanthan gum-based hydrogels XG adsorbents via acrylation with maleic anhydride and thiol-ene cross-linking to remove the gentian violet. 43 Also, graft copolymers based on XG have been effectively used for the adsorption of heavy metals and organic dyes from aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Ghorai et al 48,49 grafted acrylamide onto XG and incorporated the graft copolymer with silica nanoparticles to remove methylene blue, methyl violet and Congo red dyes from the aqueous solution. Other researchers grafted acrylamide onto xanthan gum, cross‐linked with trimethylolpropane triglycidyl ether and used it as an adsorbent to capture the crystal violet dye 50 . Njuguna et al reported on the synthesis of xanthan gum‐based hydrogels XG adsorbents via acrylation with maleic anhydride and thiol‐ene cross‐linking to remove the gentian violet 43 .…”
Section: Introductionmentioning
confidence: 99%